Evaluasi Kepatuhan PT BCA Tbk terhadap PSAK 4 dan PSAK 65 dalam Penyajian Laporan Keuangan Konsolidasi - Laras Ayu Wulandari; Rohmah Dani Andikasari; Nasywa Salma Najmi; Zarfina Fitri Aisyah; Endang Kartini Panggiarti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The purpose of this study is to examine and assess how PT BCA applies PSAK 4 and PSAK 65 in the development and presentation of its consolidated financial statements. This study is primarily motivated by the importance of consolidated financial statements as a useful source to offer a comprehensive view of an entity's financial condition, especially when the entity has subsidiaries. This research method can be categorized as descriptive qualitative research, utilizing secondary data sources, including PSAK and BCA's financial statements for the years 2022 to 2023. The findings indicate that BCA has reliably complied with PSAK 4 and PSAK 65 standards. This includes accurately combining the financial statements of its parent company and subsidiaries based on the control principle, eliminating inter-entity transactions, and transparently disclosing the NCI portion of equity. Furthermore, the fair values ​​of assets and liabilities have been combined and assessed in accordance with appropriate standards. In summary, BCA has demonstrated a strong commitment to maintaining accountability, information transparency, and effective corporate governance practices, thereby ensuring its financial statements reliably and accurately reflect the group's financial condition. From this conclusion, it can be stated that BCA has implemented both PSAKs systematically and effectively to increase reporting transparency.